2014
DOI: 10.1186/1471-2164-15-671
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome profiling of a desert evergreen shrub, Ammopiptanthus mongolicus, in response to drought and cold stresses

Abstract: BackgroundThe molecular mechanisms involved in plant tolerance to either drought or cold have been extensively studied in many plant species. However, few studies have focused on their comparisons especially using non-model plants with strong tolerance to both stresses. Ammopiptanthus mongolicus (Maxim. ex Kom.) Cheng f. is the only evergreen broadleaf shrub grown in the central Asian desert and it has very strong cold and drought tolerance. To provide further insights into plant tolerance, the transcriptome p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 62 publications
5
60
0
Order By: Relevance
“…In sugarcane plants, the drought-resistant genotype could maintain plant growth under cold and drought stress either alone or combined through enhancing the antioxidant capacity, which was not observed in the sensitive genotype (Sales et al, 2013). In the study on A. mongolicus subjected to individual cold and drought stress, genes involved in the flavonoid biosynthesis pathway were highly induced to cope with stress-induced oxidative damage (Wu et al, 2014). Both flavonoids and carotenoids belong to non-enzymatic antioxidants, which not only defend plants from oxidative damage but also show medicinal characteristics especially against human health problems (Nijveldt et al, 2001; Williams et al, 2004; Fiedor and Burda, 2014; Dani et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sugarcane plants, the drought-resistant genotype could maintain plant growth under cold and drought stress either alone or combined through enhancing the antioxidant capacity, which was not observed in the sensitive genotype (Sales et al, 2013). In the study on A. mongolicus subjected to individual cold and drought stress, genes involved in the flavonoid biosynthesis pathway were highly induced to cope with stress-induced oxidative damage (Wu et al, 2014). Both flavonoids and carotenoids belong to non-enzymatic antioxidants, which not only defend plants from oxidative damage but also show medicinal characteristics especially against human health problems (Nijveldt et al, 2001; Williams et al, 2004; Fiedor and Burda, 2014; Dani et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For example, exposure to drought or cold stress can cause inactivation of enzymes and lipid peroxidation due to the over-production of ROS. To minimize damage, cells produce antioxidants such as flavonoids to scavenge excessive ROS (Wu et al, 2014). These secondary metabolites also contribute to the specific colors, odors and tastes in plants, and are unique sources for bio-pesticides, food additives, fragrances and pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…Among the enriched GO terms, common drought‐related terms typically recovered in drought stress experiments (Fracasso et al, ; Wu et al, ; Zhang, Lei, Lai, Zhao, & Song, ) were recovered here using both control types. For up‐regulated genes, “response to water deprivation (GO:0009414)” and “response to water (GO:0009415)” were over‐represented on all days before recovery in both species.…”
Section: Resultsmentioning
confidence: 80%
“…The upregulated DEGs included a heavy representation of genes encoding ripening-related proteins, LEA proteins, peroxidases, transporters, enzymes of flavonoid biosynthetic pathways, protein kinases, ethylene receptors, and transcription factors. About 17.2% of the common DEGs had no homology to known functional proteins [82]. Similarly, Pang et al [83] identified 1620 DEGs, including 1106 upregulated DEGs and 514 downregulated DEGs.…”
Section: Findings Of Novel Genes In Native Plants From Arid Land Areasmentioning
confidence: 99%